Decreasing the Data Deficit: Improving Post-Market Surveillance in Pharmaceutical Regulation - Lemmens, Trudo; Gibson, Shannon (McGill Law Journal / Revue de droit de McGill, 2014)
The drug regulatory system is currently largely based on market-entry review of safety and efficacy data and involves only very limited post-market review. Failures in the industry-controlled production of pre-market data and the lack of solid post-market surveillance contribute significantly to highly problematic drug prescription and consumption practices, which have become a very serious public health concern. In this paper, we first discuss how historically grown drug regulations have contributed to the development of industry control over clinical trials, which is one of the key factors behind the limits of pre-market evidence. We then explore some problematic aspects related to the fixation of the drug approval system on pre-market activities, including the lack of good “real-world” evidence on drug safety; the lack of comparative evidence on patient benefit between different drugs; the lack of evidence of the safety and efficacy of off-label prescribed drugs; and the inadequate reporting of adverse drug reactions (ADRs). We argue that a more rigorous and intense post-market surveillance system could counterbalance, at least in part, the distorted situation created by the regulatory reliance on pre-market, industry-produced clinical trials data. In particular, we advocate for improvements to the current ADR reporting system, more explicit requirements for both comparative effectiveness studies and post-market clinical research in real-world settings, the promotion of transparency of pharmaceutical data, and insulating clinical research from industry control.